2013
DOI: 10.1108/qmr-06-2013-0043
|View full text |Cite
|
Sign up to set email alerts
|

Towards the conceptualisation of the antecedents of extreme negative affect towards luxury brands

Abstract: Purpose -The aim of this paper is to conceptualise the influences of extreme negative emotional response towards luxury brands as expressed in brand hate. Design/methodology/approach -The paper uses examples obtained from a critical incidents approach to interviews with a small sample of German and British luxury consumers. Informants were asked to identify extremely positive and then extremely negative incidents which affected their perceptions of luxury brands. This critical incidents approach allowed for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 46 publications
9
158
1
4
Order By: Relevance
“…Previous studies associated the Brand Hate concept with antibrand activism (Krishnamurthy & Kucuk, ; Kucuk, , ), consumer desire for revenge (Bryson, Atwal, & Hultén, ; Grégoire et al, ; Grégoire, Laufer, & Tripp, ; Johnson, Matear, & Thompson, ), shame (Johnson et al, ), brand disgust (Alba & Lutz, ), extreme form of brand dislike (Kucuk, ; Romani, Grappi, & Dalli, ), contempt and anger (Gelbrich, ; Romani, Grappi, Bagozzi, & Barone, ). Because the concept covers a broad range of negative emotions (Zarantonello et al, ) there is a need for broader definitions of Brand Hate.…”
Section: Defining Consumer Brand Hatementioning
confidence: 99%
“…Previous studies associated the Brand Hate concept with antibrand activism (Krishnamurthy & Kucuk, ; Kucuk, , ), consumer desire for revenge (Bryson, Atwal, & Hultén, ; Grégoire et al, ; Grégoire, Laufer, & Tripp, ; Johnson, Matear, & Thompson, ), shame (Johnson et al, ), brand disgust (Alba & Lutz, ), extreme form of brand dislike (Kucuk, ; Romani, Grappi, & Dalli, ), contempt and anger (Gelbrich, ; Romani, Grappi, Bagozzi, & Barone, ). Because the concept covers a broad range of negative emotions (Zarantonello et al, ) there is a need for broader definitions of Brand Hate.…”
Section: Defining Consumer Brand Hatementioning
confidence: 99%
“…Research is not clear about moral avoidance and its consequences, while numerous studies have examined moral avoidance and found different outcomes. Bryson et al [12] create no evidence that moral avoidance can lead to brand hate, while other studies did found evidence that moral avoidance can certainly lead to brand hate [46]. H3: Ideological incompatibility has a significant negative effect on brand equity…”
Section: Ideological Incompatibility and Brand Equitymentioning
confidence: 95%
“…Brand hate and brand avoidance have both been knotted to the meaning of intentionally avoiding or refusing a brand, yet only brand hate has been related to display behaviors like articulation negative feelings, refusing, or damaging company property. Likewise Bryson et al [12] entitle that brand hate is like the exciting undesirable emotional component of assertiveness to a brand. H4: Brand hate mediates the relationship between unmet expectations and brand equity.…”
Section: Brand Hate As Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the increasing spread of anti-branding sites [4] is one of the clearest manifestations of the increased power of consumers [5]. Brand hate is a negative intense emotional state capable of influencing the consumers' relationship and attitude toward certain brands and their related companies [6]. Although today the analysis of the literature provides useful insights and interesting suggestions about the phenomenon of brand hate, especially in the Italian context, there are very few studies and scales that are capable of measuring this phenomenon.…”
Section: Introductionmentioning
confidence: 99%